Numerical modeling of a large underground powerhouse using geomechanical parameters obtained by artificial intelligence techniques - Miranda, Tiago F. S. (2004)
A large underground hydroelectric scheme is being built as a power reinforcement of an exis-tent scheme completed in 1951 and located in the North of Portugal. This new scheme includes important underground works such as hydraulic circuit with about 4.4km length and two caverns for the powerhouse complex. The rock mass is predominantly granite. The geomechanical parameters of these formations wereobtained through a software called GEOPAT based in artificial intelligence techniques. This software permitsto calculate the geomechanical parameters for underground structures in granite masses. Using the obtained parameters numerical models were developed for the behaviour analysis of the powerhouse complex. Thepredicted, numerical results are compared with the corresponding monitored values showing in general a good agreement.